Unitary Operators and Variational Approaches for One-Dimensional Hamiltonians - Bozzolo, G. (1988)
Several variational approaches for the one-dimensional Schrodinger equation are devised by recourse to suitable expansions of the unitary operator that relates the corresponding eigenstates of the harmonic oscillator. A connection with the virial theorem, via scaling properties is established and an application to the ring puckering motion is discussed.